Gastrointestinal Bleeding in Left Ventricular Assist Device: Octreotide and Other Treatment Modalities. Issue 4 (July 2018) - Molina, Tara L.; Krisl, Jill C.; Donahue, Kevin R.; Varnado, Sara
Abstract : Left ventricular assist devices (LVADs) offer a therapeutic strategy for patients with end-stage heart failure. Increased device utilization has also increased the incidence of device-related complications including gastrointestinal bleeding (GIB). Multiple mechanisms have been proposed in the pathophysiology of continuous-flow LVAD-associated GIB including physiologic changes associated with high shear and nonpulsatile flow such as gastrointestinal arteriovenous malformations and acquired von Willebrand syndrome. Strategies to minimize the morbidity and mortality of LVAD-associated GIB are needed. Octreotide, a somatostatin analogue, has been described as an adjunct to current therapies and interventions. Factors that contribute to LVAD-associated GIB may be targeted by the pharmacologic effects of octreotide, including improved platelet aggregation, increased vascular resistance, and decreased splanchnic circulation. Octreotide has demonstrated clinical benefit in several case series and clinical trials for the treatment of LVAD-associated GIB. The focus of this article will be to review the pathophysiology of LVAD-associated GIB, discuss pharmacologic and nonpharmacologic treatment modalities, and review available literature on the role of octreotide in the management of LVAD-associated GIB.